Corporate social responsibility and consumer advocacy behaviors: The importance of emotions and moral virtues - Castro-González, Sandra; Bande Videla, Belén; Fernández-Ferrín, Pilar; Kimura, Takuma (Journal of Cleaner Production, 2019)
Although previous studies revealed the positive perception effect of corporate social responsibility (CSR) on consumer behavior, the influence mechanism and the impact of individual characteristics on the effect have been underexplored. The purpose of this study is not only to examine the mediating role of the emotion of admiration in the relationship between consumer perception of CSR and advocacy behaviors but also to explore the moderating role of the consumer moral virtue of integrity in the relationship between CSR perception and feelings of admiration. Data was collected from customers of a food company located in Spain, and the results show that the company's CSR practices positively influence consumer advocacy behaviors both directly and indirectly through consumer admiration for the company. Consumer integrity moderates the relationship between consumer perception of CSR and admiration. Specifically, CSR practices have a stronger admiration effect on consumers who are high in integrity. The overall importance of consumer perceptions of CSR suggest that, in the food industry, the perception of appropriate CSR practices has a positive impact on consumer attitudes and behaviors, which are also conditioned by individuals' moral virtues.
Keywords: admiration; advocacy behaviors; consumer; corporate social responsibility; integrity; Scopus; JCR